2016
DOI: 10.1515/cclm-2016-0840
|View full text |Cite
|
Sign up to set email alerts
|

Urinary orosomucoid: a novel, early biomarker of sepsis with promising diagnostic performance

Abstract: The early and relevant increase of u-ORM in sepsis suggests that it might be a promising novel marker of sepsis and could be a valuable part of routine laboratory and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In order to investigate the potential clinical utility of u-CYSC measurements, a group of patients with sepsis-related AKI (n = 33), patients with chronic hypertension (n = 43) and Type 2 diabetic patients (n = 41), were also included. AKI in septic patients was established using the Kidney Disease Improving Global Outcomes guideline [12] supported by serum CYSC concentrations, similarly to others [13][14][15]. Inclusion criteria for the chronic hypertension and diabetic patient groups were: established clinical diagnosis of their treated disease, the lack of acute inflammatory conditions and other chronic disorders such as autoimmune diseases or tumors.…”
Section: Subjectsmentioning
confidence: 99%
“…In order to investigate the potential clinical utility of u-CYSC measurements, a group of patients with sepsis-related AKI (n = 33), patients with chronic hypertension (n = 43) and Type 2 diabetic patients (n = 41), were also included. AKI in septic patients was established using the Kidney Disease Improving Global Outcomes guideline [12] supported by serum CYSC concentrations, similarly to others [13][14][15]. Inclusion criteria for the chronic hypertension and diabetic patient groups were: established clinical diagnosis of their treated disease, the lack of acute inflammatory conditions and other chronic disorders such as autoimmune diseases or tumors.…”
Section: Subjectsmentioning
confidence: 99%
“…The several-fold elevation found in active CD might be in accordance with the former observations related to other inflammatory disorders. [12][13][14]16,28 This assumption is confirmed by the significant correlations of u-ORM with conventional inflammatory parameters.…”
Section: T a B L E 1 Montreal Classification Of Patientsmentioning
confidence: 68%
“…Elevated u‐ORM excretion is supposed to be in association with the activation of the immune system. The several‐fold elevation found in active CD might be in accordance with the former observations related to other inflammatory disorders . This assumption is confirmed by the significant correlations of u‐ORM with conventional inflammatory parameters.…”
Section: Discussionmentioning
confidence: 96%
“…ORM proteins could be applied as diagnostic markers for the early events of many pathological states. Elevated urinary ORM levels have been reported as biomarkers for multiple carcinomas and inflammatory diseases such as psoriasis, Crohn disease, and sepsis (39)(40)(41)(42)(43). Notably, Park et al (44) demonstrated that the urinary levels of ORM1 and ORM2 were increased in patients with RA and correlated with disease activity.…”
Section: Discussionmentioning
confidence: 99%